Thinspiration a study on thin-ideal internalization, body image satisfaction, and self esteem. - Dagangan, Marifel (2016.)
This study aimed to determine the relationship of thin-idea internalization, body image satisfaction, and self-esteem among pre-adolescents. The research design followed the correlational approach. 70 respondents were chosen through systematic random sampling and composed of preadolescents ranging from 9-12 years olds. Pearson?s R was used to determine the correlation among body image satisfaction, thin-ideal internalization, and self-esteem and Linear Regression Analysis was used to determine whether body image satisfaction and thin-ideal internalization could predict self-esteem. The results of this study only supported one of the four hypotheses proposed. Body image satisfaction was shown to be significantly associated with thin-ideal internalization which indicates that pre-adolescents who are fairly contented with their perceived body image tend to agree and follow the thin-ideals reinforced by media. Meanwhile, findings show that there is the correlation between body image satisfaction and self-esteem levels, which was postulated by hypothesis two showed a negative correlation between self-esteem and body image satisfaction. There was also no correlation between self-esteem levels and thin-ideal internalization, which was assumed by hypothesis three. Finally, the results for regression analysis showed a very low variance of self-esteem from body image satisfaction. This means that preadolescents? body image satisfaction and their internalization of the thin ideal do not determine how they regard themselves.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Pre-adolescents.